Teachers' Efforts to Provide Learning Motivation to Students - Pu'ad Maulana; Neviyarni S; Herman Nirwana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Motivation is a very important component for students so that it can support them in many ways, especially in learning. In general, a literature review consists of sections that describe theories, results and materials that are useful for research. These materials are then used as a basis for subsequent research. Motivation is an effort to encourage and maintain a person's behavior to do something with the aim of achieving certain results or goals.